Applicability of the 2D:4D ratio in identifying predispositions for combat sports - Adamczyk, J. G.; Krejpcio, M.; Boguszewski, D.; Michalak, B. (Journal of Combat Sports and Martial Arts, 2017)
Introduction. Combat sports, even though they are associated with aggressive behavior, but athletes often train how to control emotions and aggression. Thus aggression level can be one of the selection criteria for combat sports. Material and methods. The study analyzed the value of the 2D:4D ratio and the level of aggression in 102 athletes in selected combat sports: kyokushin karate (20), ITF taekwondo (22), kickboxing (19), wrestling (21), and judo (20). Furthermore, the study evaluated a control group of 76 men who did not engage in competitive sports training. Results. The athletes practicing combat sports displayed a higher 2D:4D ratio than the persons from the control group. On the other hand, the study observed significant differences (p<0.05) in the 2D:4D ratio values within the experimental group between karate and taekwondo fighters and the rest of the athletes. Conclusions. The 2D:4D ratio is a good tool that may be useful during the selection of combat sport athletes by providing indirect information about the level of testosterone during the fetal period. Combat sports, through training, have a positive impact on their practitioners, allowing the athletes to improve the control over their emotions and know themselves better, which results in reduced aggressiveness and anger towards other people.